Immuno-hematological and biochemical changes in diabetic retinopathy patient`s blood after treatment by Nd-YAG laser - Al-Zahaw, Farah A.J (Iraqi Journal of Laser, 2009)
Diabetic retinopathy is one of most important complications of diabetes mellitus that can be treated by Nd:YAG laser. Laser is used in ophthalmic practice for photocoagulation and photodisruption. The purpose of this study is to evaluate changes in immunological ,hematological and biochemical values after treatment of diabetic retinopathy by laser. Blood samples from 10 patients suffering from diabetic retinopathy were taken before and after laser treatment to coagulate retina to prevent leakage and hemorraghe to avoid deterioration of vision.In group one (4 patients = 40%), blood tests were done one day after treatment. In group two (6 patients =60%) tests were done 7 days after treatment with laser. The study showed no clear changes in the values of biochemical tests(except glucouse is already high) and hemtologyical tests (except PT, PTT, clotting time and bleeding time for those patients taking l00mg acetylsalicylic acid or warfarin) after irradiation with laser, probably because that main organs that affecting these tests or the elements that involve in these tests have not been irradiated directly. The main changes were in mmunoglobulin values which increased as noticed in both groups, because all light- induced biological effects depend on the parameters of irradiation, the results suggest that the laser irradiation may play two principal roles in immunological changes. First, is stimulation of cellular proliferation, and stimulation of cellular differentiation that is responsible for different types of immunoglobulin.The other suggestion is that laser is acting as a triggering factor which induces systematic effects through the circulation when laser interacts with living cells so it has systemic effects through circulating blood.